Kelompok Ludruk Cak Durasim (Ludruk Organisatie) di Surabaya Tahun 1933-1945 - Munifatuz Zuhriyyah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
The aim of the study was to look at the improvement of the group of Ludruk Organisatie as art performance as well as its role in the social circumstances in Surabaya. This study was a historiography study. The arrangement of historiography must be conducted through some steps of history study method such as heuristic, sources criticism, interpretation and historiography arrangement. The findings were the characteristic performed by Ludruk Organisatie such as 1) ludruk performance has no longer presented mystique elements; 2) presented nationalism symbols as the theme of the show; 3) it was presented commercially. In conclusion, the existence of ludruk was warm-welcomed by the society, especially in East Java as the entertainment as well as the heritage. Keywords: Cak Durasim, Ludruk Organisatie, Nationalism